Creating a project culture which promotes performance in the construction industry, through an organisational perspective - Kiiskinen, Linnéa; Mared, Stine (My University, 2021)
The construction industry is an industry influenced by old traditions which have characterized the culture for a long time. In recent years, this tough project culture has emerged as a reason for both shortcomings in safety and product defects in the industry and reports have been released where the project culture is highlighted as a possible solution for errors and issues regarding quality and safety management. With this in mind, the aim of this study is to investigate how to create a positive project culture in order to improve performance through an organizational perspective. This is investigated through a qualitative study where a literature review is conducted in combination with a case study. The case study is carried out in collaboration with a medium-sized construction company active in southern Sweden and consists of observations which are made by a researcher on site, as well as interviews with all employees of the company in order to get a holistic perspective. The results from the Case study are combined with the literature research and a discussion is conducted. Several areas are discussed and tensions are found in balancing hard and soft characteristics within the project culture, transactional and transformational leadership and the importance of functioning organizational routines while remaining a sense of freedom within the project. The conclusions from the study are several. Firstly a positive project culture is identified by an open climate, communicative individuals, prestigeless and honest atmosphere and is well connected to a project group's performance through, among other things, motivation and the individuals' well being. Secondly the study shows that the company being investigated prioritizes the project culture but that there are shortcomings in routines such as feedback and knowledge transfer and that there is a lack of common understanding of how each individual in a project group should work to promote a positive project culture. Finally, the importance of top management's presence and commitment and the challenge of maintaining a positive project and organizational culture despite the desire to expand the company are emphasized.
Keywords: roject culture; performance; construction management; organisational management; leadership